Lend your hand: a model of sustainable youth engagement in environmental volunteering - Abd-Rahman, Norshariani; Halim, Lilia; Syed-Abdullah, Sharifah Intan Sharina (SAGE Publications, 2025)
Climate change issues require collaboration in large-scale problem-solving initiatives like environmental volunteering. Environmental volunteerism can reduce environmental management costs, improve environmental quality and personal development of environmental volunteers. In this regard, it is essential to investigate factors leading to volunteers’ dropping out of these programmes. This can be done by examining volunteers’ sustainability intention toward environmental volunteering participation. Therefore, this study examined the dominant factors that contribute to the sustainability intention in environmental volunteering through values orientation, society norms, and perceived well-being. 356 youth environmental volunteers from Klang Valley, Malaysia, were selected as respondents. Through structural equation modeling (SEM) analysis, our findings validated three dimensions of values orientation (egoistic, altruistic and biospheric), three dimensions of society norms (requirement, cultures, and social influence) and three dimensions of environmental volunteers’ well-being (positive emotion, relationship, and achievement). The study’s findings showed that predictor variables (values orientation, society norms, and perceived well-being) contributing 72% to the intention to sustain environmental volunteering. Volunteers’ well-being is the main factor contributing to intention. Mediating analysis shows that perceived well-being was a half mediator in the relationship between values and intention. However, perceived well-being does not mediate the relationship between society norms and intention. Therefore, the environmental volunteering programmes developed need to align with youths’ values and well-being such as focusing on fun activities, competency development and expanding the network to attract volunteers to sustain their participation. This study has implications for environmental stakeholders, especially the government, environmental non-government organisations (NGOs), and education institutions in recruiting and engaging volunteers.